Pregled sodobne ginekologije in porodništva pred epidemijo covida-19 leta 2020 (University of Maribor Press, 2021)
State-of-the-art 2020 Review on Obstetrics and Gynecology in the Pre-Covid-19 Era. The scientific monograph entitled A state-of-the-art 2020 review on obstetrics and gynecology in the pre-Covid-19 era includes papers by acknowledged Slovenian and foreign experts. The monograph is divided into seven chapters. The first chapter includes 34 papers covering the field of perinatology and the latest findings in prenatal diagnostics, prevention during pregnancy, treatment of certain chronic diseases in pregnancy, as well as papers on the cesarean section and the potential consequences of this procedure. The second chapter is dedicated to general gynecology and urogynecology and demonstrates through 41 papers the novelties of surgically treating different benign conditions and diseases as well as the role of laser treatment. The latest Slovenian recommendations on treating the menopause and using emergency contraception as well as papers on treating adolescents and women in postmenopausal period have also been added to the chapter. The third chapter includes 24 papers in the field of reproductive medicine, from ART procedures and surgical treatment of infertility to contraception. The fourth chapter entitled Gynecologic Oncology also includes 23 papers demonstrating new and less radical surgical treating methods and a few novelties in diagnostics and systemic treatment of gynecologic and breast cancer. The fifth chapter includes 6 papers covering the field of genetics in gynecology and obstetrics, which is in modern treatment of women indispensable, especially in perinatology and oncology. The sixth chapter entitled Interdisciplinary topics includes 10 papers on ethical and other dilemmas emerging with new and different methods of managing and treating women. In this chapter, a renewed course of residency in gynecology and obstetrics, also including physical therapy and the importance of physical activity, is presented by the residents. The seventh chapter includes 6 papers discussing nursing and midwifery and the important step made towards an active participation of nursing care in treating women in gynecology and obstetrics. The monograph encompasses contributions of 273 authors, written at a high level of expertise, and critically reviewed by members of the editorial board and two reviewers, internationally acclaimed experts, which adds value and quality to the publication. The content-rich monograph will certainly be a worthwhile reading material for physicians and other healthcare professionals working in the field of gynecology and obstetrics as well as for the general professional public.